Reliable Financial Statements: External Auditing System or Financial Statement Insurance? - Azar, Nasrin; E-Vahdati, Sahar (Asian Journal of Accounting Perspectives, 2022)
Research Aim: This study reviews the literature to find whether financial statement insurance can be substituted for the current external auditing system. Design/ Methodology/ Approach: This article reviews how financial statement insurance (FSI) advances external audit independence, reduces audit failure, boosts audit quality, and increases the reliability of financial statements. Research finding: This study shows that the FSI system assists in mitigating the monetary relationship between auditors and the audited companies by forcing companies to purchase insurance for their financial statements. Accordingly, FSI protects investors against any losses due to any misrepresentation instead of having them audited. In this system, companies hire insurance companies, and insurance companies hire external auditors to assess the insurance premiums and policy coverages through auditing financial reports. Also, it guarantees a lack of any misrepresentation or omission in them. Theoretical contribution/ Originality: This study contributes to the literature by concluding that financial statements insurance can be an alternative to a current audit system and investigates its usability from the perspectives of the components of the system Practitioner/ Policy implication: The study results can be useful for investors in the capital markets, companies, audit firms, and insurance companies. Keywords: External Auditors; Investors; Insurance Companies; Financial Statement Insurance Type of article: Literature Review JEL Classification: M41, M42, G22